Design and Synthesis of Caffeic Amides by Structure-based Approaches - Chawannuch Mudjupa (Science Faculty of Chiang Mai University, 2019)
Novel caffeic acid amides were designed and evaluated for their antiproliferative activities against a panel of tumor cell lines. The development based on the caffeic core structure of the identified hit compound from virtual screening of 2,666 compounds against tyrosine kinase receptor. The compounds were designed by using amide to link the caffeic core with the privileged motif, thiazole via target-based approach. Molecular docking studies indicated that the designed compounds were nicely bound to the EGFR tyrosine kinase. Among the synthesized compounds, CAD1 and CAD2 exhibited potent antiproliferative activity against breast cancer MCF-7 cells with IC50 of 8.02 and 13.69 mM, respectively. The molecular mechanism was investigated and found that CAD1 and CAD2 induced cell death by apoptosis and inhibited EGFR kinase.